Comparative kinetic study of functionalized carbon nanotubes and magnetic biochar for removal of Cd2+ ions from wastewater - Ruthiraan, M.; Mujawar, Mubarak; Thines, R.; Abdullah, E.; Sahu, J.; Jayakumar, N.; Ganesan, P. (Springer, 2015)
We did a comparative study between functionalized multiwall carbon nanotube (FMWCNTs), and magnetic biochar was carried out to determine the most efficient adsorbent to be employed in the Cd 2+ ion removal. We optimized parameters such as agitation speed, contact time, pH and adsorbent dosage using design expert vrsion 6.08. The statistical analysis reveals that optimized condition for highest removal of Cd 2+ are at pH 5.0, with dosage 1.0 g, agitation speed and contact time of 100 rpm and 90 minutes, respectively. For the initial concentration of 10mg/l, the removal efficiency of Cd 2+ using FMWCNTs was 90% and and 82% of magnetic biochar. The maximum Cd 2+ adsorption capacities of both FMWCNTs and magnetic biochar were calculated: 83.33mg/g and 62.5mg/g. The Langmuir and Freundlich constants for FMWCNTs were 0.056 L/mg and 13.613 L/mg, while 0.098 L/mg and 25.204 L/mg for magnetic biochar. The statistical analysis proved that FMWCNTs have better adsorption capacity compared to magnetic biochar and both models obeyed the pseudo-second-order.